USM RECEIVES COURTESY VISIT BY JAPANESE GROUP, DISCUSS POSSIBLE COLLABORATION PLANS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 23 September 2016 – Universiti Sains Malaysia (USM) is in talks with a Japanese consultant group on the possibility of having collaborations in holding ‘Business and Sustainable Development’ programmes for the campus community.